Blind GPS localization: enhancing positioning accuracy in GPS-denied environments - Cismas, Alexandru; Cismas, Ioana; Popescu, Decebal (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
This paper presents a method for locating a subject using the triangulation method. Three drones were used to transmit signals to a point, with the research focusing on identifying and mitigating potential delays that affect the determination of Time of Arrival (ToA). The study details, through precise measurements, the delays caused by communication protocols, the execution time of instructions on microcontrollers, and the modulation time at the radio module level. The obtained results highlight the feasibility of performing measurements while acknowledging the trade-off in precision they entail.